2016
DOI: 10.1007/s00277-016-2781-0
|View full text |Cite
|
Sign up to set email alerts
|

The predictive value of selected serum microRNAs for acute GVHD by TaqMan MicroRNA arrays

Abstract: Currently, the diagnosis of acute graft-versus-host disease (aGVHD) is mainly based on clinical symptoms and biopsy results. This study was designed to further explore new no noninvasive biomarkers for aGVHD prediction/diagnosis. We profiled miRNAs in serum pools from patients with aGVHD (grades II-IV) (n = 9) and non-aGVHD controls (n = 9) by real-time qPCR-based TaqMan MicroRNA arrays. Then, predictive models were established using related miRNAs (n = 38) and verified by a double-blind trial (n = 54). We fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…The diagnostic model for miR-489, miR-671-3p, and miR-28-5p was 0.841, 85.71%, and 83.33% for the area under the receiver operating characteristic curve, positive predictive value, and negative predictive value, respectively. In addition, the predictive model for miR-374a and miR-26b, which could predict an increased risk for 1 to 2 weeks before the onset of aGVHD, was 0.722, 76.19%, and 69.70% for area under the receiver operating characteristic curve, positive predictive value, and negative predictive value, respectively [60]. Thus, miRNA panels (miR-671-3p, miR-489, miR-28-5p, miR-374a, and miR-26b) may be used as diagnostic and predictive biomarkers for grade II to IV aGVHD.…”
Section: Circulating Micrornas As Predictive Biomarkers Of Agvhdmentioning
confidence: 97%
See 3 more Smart Citations
“…The diagnostic model for miR-489, miR-671-3p, and miR-28-5p was 0.841, 85.71%, and 83.33% for the area under the receiver operating characteristic curve, positive predictive value, and negative predictive value, respectively. In addition, the predictive model for miR-374a and miR-26b, which could predict an increased risk for 1 to 2 weeks before the onset of aGVHD, was 0.722, 76.19%, and 69.70% for area under the receiver operating characteristic curve, positive predictive value, and negative predictive value, respectively [60]. Thus, miRNA panels (miR-671-3p, miR-489, miR-28-5p, miR-374a, and miR-26b) may be used as diagnostic and predictive biomarkers for grade II to IV aGVHD.…”
Section: Circulating Micrornas As Predictive Biomarkers Of Agvhdmentioning
confidence: 97%
“…Zhang et al [60] also demonstrated that miR-671-3p, miR-489, and miR-28-5p have important roles in tissue damage, tissue repair, and inflammation. Myeloid differentiation primary response gene 88 (Myd88) is an important cytosolic adaptor protein in the TLR signaling pathway, which acts as a target of miR-489 [65].…”
Section: Circulating Micrornas As Predictive Biomarkers Of Agvhdmentioning
confidence: 99%
See 2 more Smart Citations
“…Ferrara et al[ 2 ] created an algorithm that included TNFR1, ST2, and Reg3α in a prognostic score for GVHD. We and others have reported clinical findings for the prediction and diagnosis of GVHD, such as the use of mass spectrometric (MS) profiling of urine[ 3 ], serum samples [ 4 , 5 ], microRNA of peripheral blood [ 6 , 7 ] and T cells [ 8 ].…”
Section: Introductionmentioning
confidence: 99%